E-governance Framework to Measure Digital Competence of HEIs in India - Neera Chopra (European Scientific Journal, ESJ, 2019)
Today, Higher Education Institutions are using ICT to provide administration and management services, develop course materials, facilitate communication among students and increase cooperation and research. Information on how most Universities have integrated ICT and to what stage is lacking. Nevertheless, some studies indicate differences in the level of the use of ICT among HEIs. The present study discusses the framework developed by the Joint Research Centre, European Commission that can be applied to assess digital co mpetency of Higher Education Institutions in India. A questionnaire, based on the above-stated framework has been formulated to assess, analyse and ascertain the status of ICT integration on the 6 parameters – namely - Leadership and Governance Practices, Teaching and Learning Practices, Professional Development of the Teaching and Non-Teaching staff, Assessment Practices, Collaboration and Networking; and Infrastructure. The expected result will be of interest to policymakers and academicians in the field of Higher Education in India.